Design science research em gestão de operações: proposta e avaliação de um modelo de referência para projetar artefatos - Bagni, Gustavo (Universidade Federal de São Carlos, 2023)
Despite the high potential contribution of Design Science Research (DSR) in the Operations Management (OM) field, there are still few studies published using this approach. Furthermore, the reference models for conducting the DSR do not explain how to design an artefact, the central element of DSR, and do not propose alternatives for different types of DSR. This thesis begins with a systematic literature review that identifies the main characteristics of studies using DSR developed in OM and proposes the existence of two types of DSR in this field: one focused only on practical contributions and another whose objective is also to contribute to theory. Three variables distinguish these two types. Based on this characterization and the study of previous models for conducting DSR studies in the OM field, a new reference model focused on artefact design is proposed. This model combines CIMO Logic with DSR since the beginning of the study, providing a structured process of designing artefacts, reducing the time and resources required. The model also explicitly includes the relationship between kernel theories and design theory in the second mode knowledge generation process. It is suitable for both types of DSR, although for the first type the benefits are partial, as the final step is not performed (formulation of design propositions). Finally, evaluating the model through the empirical implementation of an S&OP process focused on new products (empirical situation in which the model proposed in the thesis was implemented and evaluated), the thesis contributes to this class of problems by showing that it is possible for two S&OP processes in the same organization, one focused on mature items and the other focused on new products.
Design science research in operations management: proposal and evaluation of a reference model to design artefacts
Keywords: Design science research; Pesquisa empírica; Pesquisa qualitativa; Gestão de operações; Planejamento de vendas e operações; Empirical research; Qualitative research; Operations management; Sales and operations planning; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO